DOUBLE BURDEN PADA PEREMPUAN DITINJAU DARI PERSPEKTIF HUKUM ISLAM (STUDI KASUS DI HOME INDUSTRY KERUPUK “DUA PUTRA” SINGGAHAN TUBAN) - Fahri, Herfin; Ulya, Vita Fitriatul (Al Hakam : The Indonesian Journal of Islamic Family Law and Gender Issues, 2022)
The development of the times marked by the flow of globalization has also changed the human mindset. If in the past women were considered the second sex and only took part in the domestic sector, now there are many women who play a role equal to the position of men, for example with many women who are involved in the public sector, therefore the phenomenon of double burden or double burden. often afflicts women. This study aims to explore the double burden of female workers in the "Dua Putra" cracker home industry and viewed from the perspective of Islamic law. This research is a type of qualitative research with a phenomenological descriptive approach that examines the phenomenon of double burden in Lajolor Singgahan village, Tuban. The informants are 7 women working in the home industry of "Dua Putra " crackers. The results show that there are several reasons that motivate women to work in the informal sector such as the " duaputra " cracker home industry, including to improve the economy and family welfare, and to fill spare time for productive activities so that they can increase family income even though it is enough. Islam as a religion of rahmatanlil 'aalamiin punishes women to work with 3 laws, namely allowed, forbidden and obligatory. Each law applies to women depending on the accompanying conditions.